Hello,
f(x)=x^3-11x²+36x-36
y-intercept
x=0==>y=-36
x-intercepts
f(2)=2^3-11*4+72-36=8-44+36=0
f(x)=(x-2)(x²-9x+18)
g(x)=x²-9x+18
g(3)=3²-9*3+18=0
g(x)=(x-3)(x-6)
f(x)=(x-2)(x-3)(x-6)
f'(x)=3x²-22x+36=(x-(11+√13)/3)(x-(11-√13)/3)
x≈4,8685... or x≈9,7981
Answer:
(5, - 6)
Step-by-step explanation:
Given the 2 equations
6x + 3y = 12 → (1)
6x - 5y = 60 → (2)
Multiply (2) by - 1 and add to (1) will eliminate the term in x
- 6x + 5y = - 60 → (3 )
Add (1) and (3) term by term
(6x - 6x) + (3y + 5y) = (12 - 60)
8y = - 48 ( divide both sides by 8 )
y = - 6
Substitute y = - 6 into (1) or (2) and siolve for x
Using (1), then
6x - 18 = 12 ( add 18 to both sides )
6x = 30 ( divide both sides by 6 )
x = 5
Solution is (5, - 6)
Answer: B. $32.50
Step-by-step explanation:
The premiums listed in brackets are for every $25,000 of coverage.
Mateo wants a $100,000 coverage so we need to divide this by $25,000 to see how much more he will have to pay:
= 100,000 / 25,000
= 4
Mateo will have to pay 4 times the $5.50 for himself:
= 4 * 5.50
= $22.00
For his spouse who requires $75,000, he will have to pay:
= 75,000 / 25,000
= 3
= 3 * 3.50
= $10.50
Total Mateo is to pay for both his spouse and himself is:
= 22 + 10.5
= $32.50
Slope intercept form is y=mx+b
y=-x+700